The physical demands of Major League Soccer match-play with specific reference to high-intensity activity by position, venue and opposition quality - Collins, J. J.; Fernandez Navarro, J.; McRobert, A. P.; Silvers-Granelli, H.; Malone, S.; Collins, K. D. (PLOS ONE, 2025)
This study examined the running loads of Major League Soccer matches across three seasons. Data was obtained from 1243 individual matches which included 800 players (26 ± 1.1 years) from 28 teams. Data was collected via optical tracking system. All data from players who completed at least 85-minutes of match play were included. Physical performance measures included total distance (m) (TD), high-speed running (19.8-25.2 km · hr1) (HSR), sprint distance (>25.2 km · hr1) (SpD), sprint efforts (n) and high-intensity running (>19.8 km · hr1) (HID). Data was analysed to observe the average match running loads of the measures of physical performance as a whole and within the respective positions, temporal and seasonal. The data was processed using R statistical software. Linear mixed models were used to analyse statistical significance. The average total distance covered was 9950 ± 990m. The average high-speed running 519 ± 171m, whereas the average sprint distance was 166 ± 98. The average sprints (n) were 10 ± 5. CM cover the most total distance (10510 ± 1000m) while full backs and wide midfielders cover the most high-speed running and sprint distance (599 ± 147; 225 ± 98m). Contextual factors such as quality of opposition and venue have an impact on the movement demands of match-play with players covering less TD against higher ranked teams and higher SpD and HID with teams of weaker opposition. However, players performed less TD and SpD when playing away. Furthermore, signifying the importance of understanding a teams` principles of play and their affect on match running loads.